Examining the Mediating Role of Consumer Satisfaction in the Relationship between Product Quality and Repurchase Decisions: A Study of Skintific Skincare in Makassar - Ilyas, Suci Ramadhani; Wardhana Haeruddin, Muhammad Ilham; Aswar, Nurul Fadilah; Riu, Isma Azis; Musa, Chalid Imran (CV. Lafadz Jaya, 2026)
This study examines the mechanism through which product quality influences repurchase decisions by analyzing the mediating role of consumer satisfaction in the skincare industry. Grounded in the Stimulus-Organism-Response (S-O-R) framework, product quality is conceptualized as a stimulus, consumer satisfaction as an organismic state, and repurchase decision as a behavioral response. Data were collected from 120 consumers of Skintific skincare products in Makassar City using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that product quality has a significant positive effect on consumer satisfaction but does not directly influence repurchase decisions. In contrast, consumer satisfaction exerts a strong and significant effect on repurchase decisions and fully mediates the relationship between product quality and repurchase behavior. These findings suggest that in experience-driven and highly competitive skincare markets, perceived product quality alone is insufficient to generate repeat purchases unless it is internalized through positive post-consumption evaluations. This study contributes to consumer behavior literature by extending the application of the S-O-R framework to post-consumption decision-making and by emphasizing consumer satisfaction as a central psychological mechanism driving repurchase behavior. Managerially, the findings highlight the importance of delivering consistent and meaningful usage experiences to strengthen long-term consumer loyalty